(untitled) (Tạp chí Y học Cộng đồng, 2026)
Abstract: Peptic ulcer disease is a common condition worldwide and in Vietnam. In 2019, the global prevalence of peptic ulcer disease was approximately 8.09 million cases, an increase of 25.8% compared to 1990. Research objectives: Determine the proportion of knowledge about preventing the recurrence of gastric and duodenal ulcers. Research methods: A descriptive cross-sectional study was conducted on 96 patients. The study subjects were patients diagnosed with peptic ulcer disease who were receiving outpatient treatment at the Department of General Examination, Tra Vinh Provincial General Hospital. The study was carried out from May 6 to July 12, 2024. Location: Outpatient Clinic, Department of General Examination, Tra Vinh Provincial General Hospital. Results: 53.1% of patients had correct knowledge about the role of prevention in the recurrence of peptic ulcer disease. Conclusion: Health workers should pay more attention to providing health education to patients on preventing the recurrence of peptic ulcer disease, thereby improving treatment effectiveness and ensuring patients’ health.